Transformasi perpustakaan berbasis inklusi sosial pada Rumah Baca Asma Nadia - Wiwit Widyawati; Yunus Winoto (IAIN Padangsidimpuan, 2022)
The social inclusion -based library transformation is a change in library services that is committed to improving the quality of life and well -being of its users. Asma Nadia reading house is a community reading garden pioneered by a famous book author Asma Nadia. Initially, this book reading house was established in Cianjur Regency, West Java, but now it has spread throughout Indonesia with a number of about 254 reading houses. The purpose of this study is to examine the progress of the Asma Nadia reading house in an effort to improve the quality of life and well -being of the community through a pilot program of reading houses to various regions in Indonesia. The method used in the study uses a qualitative approach with the type of case study research. Data collection techniques were performed through observations, interviews and literature studies. As for the analysis technique, it is done through three stages, namely the stage of data reduction, data presentation and the stage of verification and drawing conclusions. Based on the results of the research, it is known that the transformation of the library by Asma Nadia reading house was done through various changes such as pioneering movement and development of reading houses to various regions in Indonesia, providing reading materials to each reading house, doing various service innovations in attracting people to read.